A 3'UTR Polymorphism of IL-6R Is Associated with Chinese Pediatric Tuberculosis. (19th March 2014) - Shen, Chen; Qi, Hui; Sun, Lin; Xiao, Jing; Yin, Qing-qin; Jiao, Wei-wei; Wu, Xi-rong; Tian, Jian-ling; Han, Rui; Shen, A-dong
Abstract : Background . IL-6 is a proinflammatory cytokine that plays a critical role in host defense against tuberculosis (TB). Genetic polymorphisms of IL-6 and its receptor IL-6R had been discussed in adult TB recently. However, their role in pediatric TB is still unclear. Due to the obvious differences in TB pathophysiology in children, which may also reflect differences in genetic background, further association studies in pediatric populations are needed. Methods . A case-control study was carried out in a Chinese pediatric population including 353 TB patients and 400 healthy controls. Tag-SNPs of IL-6 and IL-6R genes were selected by Haploview software, genotyped using MassArray, and analyzed statistically. Results . One polymorphism, rs2229238, in the 3'UTR region of IL-6R was observed to be associated with increased resistance to TB (adjusted P = 0.03). The rs2229238 T allele contributed to a reduced risk to TB in recessive heritable model (OR, 0.53; 95% CI, 0.35–0.78). Conclusions . By tag-SNP genotyping based case-control study, we identified a genetic polymorphism in the IL-6R 3'UTR that regulates host resistance to pediatric TB in a Chinese population.